The Influence of Strategic Innovation Management (SIM) Practices on the Industrial Sector Financial Performance - Gharibeh, Muna (Journal of Social Sciences (COES&RJ-JSS), 2019)
The present study sought to examine the impact of the strategic innovation management (SIM) practices on the organizational financial performance among the industrial sector in Jordan. However, the study sample is (92) respondent from management of four Jordanian industrial firms, which is listed in Amman stock Exchange. The determinants of SIM practices are HR innovation, product innovation, firm structure innovation and research and development innovation. However, the financial performance includes net assets, return on assets (ROA), leverage and profits. The statistical package for social sciences (SPSS) is used for data analysis. The study found that SIM practices have positive impact on enhancing the firm's financial performance; increasing the return on assets (ROA) and the profits, and decrease the leverage. This result presented by coefficient of correlation (0.78) which refers to a positive relationship between SIM and financial performance. The research recommends further research on products innovation; due its effectiveness in generating new products and enhances the firm's competitive advantage and performance.